2017
DOI: 10.5114/pg.2017.72096
|View full text |Cite
|
Sign up to set email alerts
|

Management of anemia in inflammatory bowel disease: a challenge in everyday clinical practice

Abstract: Anemia is the most common extraintestinal manifestation and complication of inflammatory bowel disease (IBD). Its etiology is multifactorial and mostly is a combination of iron deficiency anemia (IDA) and chronic anemia (ACD). Because of its high incidence in patients with IBD and its influence on their quality of life, regular screening is recommended. In case of IDA type of medication and route of administration should be determined by many factors such as general condition of the patient, IBD activity or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
(29 reference statements)
0
12
0
7
Order By: Relevance
“…We also reported that in this patients the female gender did not affect the incidence of venous thromboembolism. The management of inflammatory bowel disease is challenging because of its atypical pathophysiological mechanism, co-existing morbidities, and manifestations (49)(50)(51). Higher predisposition to venous thromboembolic events is one of the common co-morbidities of patients affected with inflammatory bowel disease (15,20,21) and is associated with poor prognostic outcome in terms of short-, long-term morbidity and mortality (22,52).…”
Section: Discussionmentioning
confidence: 99%
“…We also reported that in this patients the female gender did not affect the incidence of venous thromboembolism. The management of inflammatory bowel disease is challenging because of its atypical pathophysiological mechanism, co-existing morbidities, and manifestations (49)(50)(51). Higher predisposition to venous thromboembolic events is one of the common co-morbidities of patients affected with inflammatory bowel disease (15,20,21) and is associated with poor prognostic outcome in terms of short-, long-term morbidity and mortality (22,52).…”
Section: Discussionmentioning
confidence: 99%
“…Iron dextran, also a high molecular weight-infused preparation, showed a similar reduction in cFGF23 in response to FCM with no change in iFGF23. Many other case reports have emerged in different patient populations receiving FCM that have exhibited hypophosphatemia due to significant elevations of iFGF23 (93)(94)(95)(96). These studies demonstrated that specific carboxyhydrate ligands reduce the ability to cleave iFGF23 into its inactivated fragments.…”
Section: B Iron Supplementationmentioning
confidence: 96%
“…The second cause is anaemia of chronic disease, connected with negative impact of pro-inflammatory cytokines on erythropoiesis and shortened red blood cell survival. Vitamin B 12 and folic acid deficiencies, use of potentially myelotoxic drugs, and haemolysis may also contribute [811].…”
Section: Introductionmentioning
confidence: 99%